2008
DOI: 10.1029/2008jd009863
|View full text |Cite
|
Sign up to set email alerts
|

Net ecosystem fluxes of isoprene over tropical South America inferred from Global Ozone Monitoring Experiment (GOME) observations of HCHO columns

Abstract: [1] We estimate isoprene emissions over tropical South America during 1997-2001 using column measurements of formaldehyde (HCHO) from the Global Ozone Monitoring Experiment (GOME) satellite instrument, the GEOS-Chem chemistry transport model, and the MEGAN (Model of Emissions of Gases and Aerosols from Nature) bottom-up isoprene inventory. GEOS-Chem is qualitatively consistent with in situ ground-based and aircraft concentration profiles of isoprene and HCHO, and GOME HCHO column data (r = 0.41; bias = +35%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
151
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(158 citation statements)
references
References 99 publications
(221 reference statements)
7
151
0
Order By: Relevance
“…Over region South American Tropical, instead of peaking at 4.2 TgHCHO in August only like the prior, the posterior estimates peak at 2 TgHCHO in April (wet season) and at 2.1 TgHCHO in September (dry season). Interestingly, this posterior seasonal cycle agrees well with the in-situ tower measurements of isoprene, also showing two peaks, made for year 2002 at Tapajos National Forest in Brazil (Barkley et al, 2008, their Fig. 8).…”
Section: Regional Budget and Comparison With Recent Studiessupporting
confidence: 74%
See 4 more Smart Citations
“…Over region South American Tropical, instead of peaking at 4.2 TgHCHO in August only like the prior, the posterior estimates peak at 2 TgHCHO in April (wet season) and at 2.1 TgHCHO in September (dry season). Interestingly, this posterior seasonal cycle agrees well with the in-situ tower measurements of isoprene, also showing two peaks, made for year 2002 at Tapajos National Forest in Brazil (Barkley et al, 2008, their Fig. 8).…”
Section: Regional Budget and Comparison With Recent Studiessupporting
confidence: 74%
“…The largest discrepancies are found over the tropical regions, and particularly over South America and Indonesia. This has already been pointed out by Barkley et al (2008), who found higher model HCHO columns (using the GEOS-Chem chemistry-transport model and the MEGAN inventory for NMVOC emissions) than GOME HCHO measurements. HCHO concentrations are mainly driven by NMVOC emissions and the uncertainties associated with these NMVOC emissions (e.g.…”
Section: Prior and Posterior Hcho Total Columns And Fit To Omi Obsermentioning
confidence: 63%
See 3 more Smart Citations